IMPACT OF ULTRA-PROCESSED FOOD CONSUMPTION ON THE RISK OF OBESITY IN THE PRODUCTIVE AGE GROUP - LITERATURE REVIEW - Azzahra, Salsabila; Rachman, Helwa; Krismawanti, Agisna Rafa; Nurul Azizah, Nazhifa; Pasaribu, Christiani; Ariyanto, Januar (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Consumption of UPFs continues to increase with the development of the food industry and urbanization. UPFs are high in calories, fat, sugar, additives, and low in nutrients. Excessive intake of these foods leads to an energy surplus in the body, which can trigger fat accumulation and increase the risk of obesity. This study aims to examine the relationship between UPF consumption and the risk of obesity in productive-age Indonesians. This study employed a qualitative method through a literature review, analyzing scientific articles related to UPF and obesity in productive age groups from 2020 to 2025. The literature was searched online, selected based on inclusion criteria, and analyzed descriptively and qualitatively using a thematic approach. The study results show that most studies found a significant association between UPF consumption and an increased risk of obesity. Factors contributing to high consumption of ultra-processed foods among those of productive age include easy access, attractive packaging, delicious taste, low price, and convenient preparation. Psychological factors such as the reward system and dopamine play a role in regulating eating behavior and may encourage UPF consumption. High consumption of UPF is a major risk factor for obesity in the productive age group. Nutrition education, regulation of UPF product promotion, strengthening of labeling policies, and increased access to healthy foods are needed to reduce UPF consumption and reduce the prevalence of obesity in the productive age group.